Gross Total Resection of a Recurrent in-and-around Cavernous Sinus Meningioma through a Combined Transcavernous Anterior and Middle Infratemporal Fossa Approach with Extracranial-Intracranial Bypass - Nonaka, Yoichi; Hayashi, Naokazu; Fukushima, Takanori (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objectives The study aims to describe surgical management of an invasive cavernous sinus meningioma with a combination of several skull base approaches and bypass surgery.Design This study is an operative video.Results Resection of the recurrent skull base meningioma is still challenging, especially if the tumor involves or encases the carotid artery. Cerebral bypass surgery is an essential adjunct in the armamentarium of skull base surgery when vessel reconstruction is required. In this paper, we describe our experience of successful treatment of an invasive recurrent skull base meningioma, which involved the entire cavernous sinus and the internal carotid artery. A 46-year-old woman presented with a 2-year history of gradually worsening left-sided exophthalmos and visual impairment. The patient had previously undergone two craniotomies for resection of the left-sided spheno-orbital meningioma. Pathological diagnosis was chordoid meningioma, which is classified as an intermediate-grade meningioma. The second surgery had been performed for a rapid tumor regrowth 6 months after the first surgery. The patient lost her left-side vision after the second surgery. Aggressive tumor regrowth was confirmed with extension into the left orbit, infratemporal fossa, and cavernous sinus with engulfment of the carotid artery. A balloon occlusion test revealed intolerance of the left internal carotid artery occlusion. Considering the patient's age, tumor behavior, and intolerance of the carotid artery of the lesion side, we scheduled gross total resection of the tumor with vessel reconstruction.Conclusion Although cerebral bypass surgery is a technically challenging procedure, it plays an important role in the surgical management of the complex vessel-engulfing tumor.The link to the video can be found at https://youtu.be/GCmpxK3hW18.
Keywords: cavernous sinus; cerebral bypass; recurrent meningioma; skull base surgery; transcavernous approach